Recent advances in nuclear actin research - Anikó Szabó; Péter Borkúti; Zoltán Kovács; Ildikó Kristó; Péter Vilmos (Nucleus)
Actin was first observed in the nucleus more than sixty years ago but research on nuclear actin did not receive significant attention for the next forty years. It only started to accelerate around the year 2000, when the first convincing experimental data emerged indicating that actin participates in essential nuclear processes. Today, we know that actin is involved in transcription, replication, DNA repair, chromatin remodeling, and participates in the determination of nuclear shape and size. In this paper we review the results of the last five years of increasingly intensive research on nuclear actin, because on one hand, the field has expanded with several new directions during this time, and on the other hand, the enrichment of our picture of nuclear actin will certainly provide a more solid foundation and new impetus for its future investigation.